Prinzipien und Aspekte der Seuchenalarmplanung am Beispiel der Influenzapandemieplanung - Haas, W. H. (Bundesgesundheitsblatt Gesundheitsforschung Gesundheitsschutz, 2005)
Despite significant medical progress, recent events have shown that infectious diseases have not lost significance. Indeed, the threat of worldwide epidemics has increased. Due to their high infectious ness and rapid person-to-person transmissibility, the emergence of new influenza viruses with pandemic potential poses an especially alarming situation in this regard. The world population would be “immunologically naïve” to a new pandemic virus, permitting explosive spread of the disease. During the last century, three influenza pandemics have demonstrated that this is not merely a hypothetical risk. Currently it is feared that the possible human adaptation of avian influenza viruses that have recently become endemic in birds in Southeast Asia could result in a new pandemic strain. With the publication of the German Influenza Pandemic Preparedness Plan, preparation for this potential threat has reached an important stage in Germany. The implementation of the plan, which includes measures that go beyond the scope of public health, must now proceed swiftly. The long-term goal of pandemic preparedness planning is to be better equipped to deal with potential health threats in general, in particular those ensuing from the emergence of new infectious diseases under conditions of a growing global network.